OPTIMALISASI SINERGI ANTARA PEMERINTAH DAN GEREJA DALAM PERENCANAAN ANGGARAN UNTUK KEGIATAN KEAGAMAAN KRISTEN DI KOTA BATAM - Purba, Gomgom (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2025)
This study aims to explore and analyze the optimization of synergy between the government and the church in budget planning for Christian religious activities in Batam City. Religious activities play a vital role in character building and maintaining harmony among citizens. While the church serves as a center for moral and social development and the government has a constitutional responsibility to support religious freedom, challenges in creating optimal synergy still exist. The lack of clarity in roles between the government and the church, as well as inadequate coordination mechanisms, hinder collaboration. This research utilizes a qualitative method with a case study approach to gather data through in-depth interviews and document analysis. The findings indicate that effective synergy can be achieved through participatory budget planning involving both parties from the outset, as well as the application of innovations in budgeting schemes and transparency principles. The recommendations produced from this research include establishing a Permanent Consultation Forum between the Government and the Church, creating special budget categories for social-religious activities, and developing technical guidelines for partnership. Through these measures, it is expected that the synergy between the government and the church will provide positive impacts for the multicultural community of Batam City, creating a more harmonious environment and optimizing the quality of life for its residents.